The Archaeology of the Outposts of Steinaecker’s Horse, a British Volunteer Unit during the Anglo-Boer War (1899-1902) - Van Vollenhoven , Anton C (Scientia Militaria - South African Journal of Military Studies, 2025)
Steinaecker’s Horse was a volunteer unit which fought on the side of the British during the Anglo-Boer War. The members of the unit consisted of local inhabitants of the Lowveld (now part of Mpumalanga) including Swazi, Pedi, and Shangane soldiers, but a few British soldiers joined their ranks. They operated in the Lowveld and Swaziland with the main aim of preventing the Boers from contacting supporters in Portuguese East Africa. The unit established a number of outposts for this purpose. The history of Steinaecker’s Horse has been studied over the past few years. Historical sources on the unit are scarce and thus they were supplemented by archaeological excavations. The artefacts excavated provide information about the lifestyle and everyday circumstances of the soldiers, as well as their interaction with local people. It seems that outposts were placed close to existing communities, probably so that these people could be employed as scouts, servants, cooks, and hunters. Together with artefacts linked to British soldiers, such as ammunition and porcelain, objects linked to local people have been identified at all sites. These include ceramic pottery, glass beads and traditional weapons. Furthermore, the amount of faunal remains excavated at these outposts indicate that the inhabitants supplemented their diet by eating game. Since most of the occupations held by members of Steinaecker’s Horse before the war are known, some of the excavated artefacts can be linked to such professions, which may have served the unit. This includes inter alia tailors, barbers, blacksmiths, cooks, and musicians.